Robust Trend Estimation for AR(1) Disturbances - Roland Fried; Ursula Gather (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
We discuss the robust estimation of a linear trend if the noise follows an autoregressive process of first order. We find the ordinary repeated median to perform well except for negative correlations. In this case it can be improved by a Prais-Winsten transformation using a robust autocorrelation estimator. – – Wir behandeln die robuste Schätzung eines linearen Trends bei autoregressiven Fehlern erster Ordnung. Die Repeated Median Regression zeigt ein gutes Verhalten bei positiven Korrelationen. Bei negativen Korrelationen ist eine Verbesserung durch eine Prais-Winsten Transformation mittels eines robusten Korrelationsschätzers möglich.
Keywords: 519; Robust Regression; Autocorrelations; Detrending; Cochrane-Orcutt Estimator; Prais-Winsten Estimator; Regression; Robustes Verfahren; Autokorrelation; Theorie